Quick Reference Guide to Postemergence Herbicides for Citrus Weed Control - Ramdas Kanissery; Camille E. McAvoy; Jamie D. Burrow; Stephen H. Futch; Brent A. Sellers; S. Shea Teems (EDIS, 2021)
This quick reference table will provide growers with information (suggested rates, use restrictions, etc.) on different herbicides used in citrus. The herbicide table, prepared based on the Florida Citrus Production Guide, will aid growers to select an appropriate postemergent herbicide program in citrus groves. Written by Ramdas Kanissery, Camille E. McAvoy, Jamie D. Burrow, Stephen H. Futch, Brent A. Sellers, and S. Shea Teems, and published by the UF/IFAS Horticultural Sciences Department. https://edis.ifas.ufl.edu/hs1410